Clinical Effect of Screw Internal Fixation on Fracture Healing and Ankle Alignment in Patients with Posterior Malleolar Fracture - Zhou, Jiawang; Wu, Weidong; Sun, Li; Lv, Feng; Fan, Junjie (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: To examine the clinical impact of screw internal fixation on the process of fracture healing and ankle alignment in individuals diagnosed with posterior malleolar (PM) fracture, specifically those with a fracture involving less than 25% of the articular surface (ASR) area. MATERIAL AND METHODS: A total of 120 patients diagnosed and treated for PM fracture, encompassing less than 25% of the distal tibial ASR area, were selected from our hospital's records spanning from September 2021 to June 2023. These people were subsequently divided into two groups, namely the control group (group A) and the observation group (group B), based on the distinct treatment methods employed, with each group consisting of 60 patients. The people in the group A were treated with posterior malleolus non internal fixation, while the patients in the group B were treated with posterior malleolus screw internal fixation. The visual analog scores, peak plantar pressure and AOFAS scores of the two groups were subjected to comparison. RESULTS: The visual analog scores in the observation group at 6 months and 12 months after operation were reduced than the group A. Three months after operation, the peak plantar pressure of the affected foot (full foot, hind foot) in the group B was reduced than that of the healthy foot; There was a lack of statistically significant variation observed in the peak plantar pressure (full foot, hind foot) between the affected foot and the healthy foot 12 months after operation in the group B, and the plantar pressure tended to be balanced. Three months after operation, the peak plantar pressure of the affected foot (full foot, hind foot) in the group A was reduced than that of the healthy foot; After a period of 12 months following the surgical procedure, no notable disparity in the maximum pressure exerted on the sole of the foot was observed between the foot that underwent the operation and the unaffected foot in the group A, but the peak plantar pressure of the whole foot was reduced than that of the healthy foot, and the plantar pressure did not tend to be balanced. At the intervals of 6 months and 12 months following the surgical procedure, AOFAS ankle hind foot score in the group B was increased than the group A. CONCLUSIONS: The utilization of screw internal fixation demonstrates favorable clinical outcomes in patients presenting with PM fracture encompassing less than 25% of the articular surface area, which is conducive to promoting fracture healing, maintaining good ankle alignment, and promoting patient rehabilitation. KEY WORDS: screw internal fixation, posterior ankle fracture, articular surface of distal tibia, fracture healing, ankle joint alignment.
Keywords: dospělí; Fracture Healing; Ankle Fractures; Female; hojení fraktur; Adult; výsledek terapie; ženské pohlaví; kostní šrouby; lidé; Treatment Outcome; hlezenní kloub; Male; Ankle Joint; vnitřní fixace fraktury; lidé středního věku; mužské pohlaví; Middle Aged; Fracture Fixation, Internal; Bone Screws; fraktury kotníku; Humans